2022
DOI: 10.1002/ar.24997
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical plasticity of the carotid body in hypertension

Abstract: The carotid body (CB), a main peripheral arterial chemoreceptor, has lately been implicated in the pathophysiology of various cardiovascular disorders. Emerging experimental evidence supports a causal relationship between CB dysfunction and augmented sympathetic outflow which is the common hallmark of human sympathetic‐related diseases, including essential hypertension. To gain insight into the neurotransmitter profile of chemosensory cells in the hypertensive CB, we examined the expression and cellular locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Chronic hypoxia also induces profound changes in other neurochemical systems within the CB such as catecholaminergic, peptidergic and nitrergic systems [23]. Our recent data have indicated that the nitrergic and neurotrophic profile of the CB cell population is also altered in hypertension and this may activate its chemosensitivity [5].…”
Section: Neurochemical Plasticity Of the Human Cb At High Altitudementioning
confidence: 98%
“…Chronic hypoxia also induces profound changes in other neurochemical systems within the CB such as catecholaminergic, peptidergic and nitrergic systems [23]. Our recent data have indicated that the nitrergic and neurotrophic profile of the CB cell population is also altered in hypertension and this may activate its chemosensitivity [5].…”
Section: Neurochemical Plasticity Of the Human Cb At High Altitudementioning
confidence: 98%
“…In this special issue, Dainius Pauza and colleagues from the Lithuanian University of Health Sciences in Kaunas (Lithuania) share their long‐standing expertise and further elaborate on the comparative anatomy of the cardiac and epicardiac innervation as well on the cardiac conducting system validating several models for cardiac research and cardiac pathology (Inokaitis et al, 2023; Pauziene et al, 2023; Saburkina et al, 2023). This part on the autonomic innervation of the heart is further complemented by a review article from Filipovic and collaborators from the University of Split (Croatia) on our current knowledge of the pathophysiological mechanisms and diagnostic approaches related to cardiac autonomic neuropathy (Filipovic et al, 2023), by a joint study from the Bulgarian Academy of Sciences, the Trakia University in Stara Zagora and the Medical University of Sofia demonstrating the neuronal plasticity displayed by the carotid body in hypertension (Atanasova et al, 2023) and by a contribution of Vakhrushev et al (2023) dealing with the significant contribution of ANS dysfunction to the development of cardiovascular diseases such as arterial hypertension, coronary artery disease and chronic heart failure. In most cases the observed symptoms are due to an increase in sympathetic activity and a decrease in parasympathetic activation.…”
Section: Pioneering Historical Contributions On the Autonomic Nervous...mentioning
confidence: 99%
“…Other similarities between HF and hypertension are the changes in NOS-NO and Ang II-AT 1 R pathways. Atanasova et al (2020Atanasova et al ( , 2022 have demonstrated that SHRs have impaired carotid body NO production with a marked reduction of protein expression for both nNOS and eNOS in both chemoreceptor cells and blood vessels.…”
Section: Mechanisms Of Carotid Body Dysfunction In Hypertension and H...mentioning
confidence: 99%
“…Atanasova et al. (2020, 2022) have demonstrated that SHRs have impaired carotid body NO production with a marked reduction of protein expression for both nNOS and eNOS in both chemoreceptor cells and blood vessels. NO is an essential negative modulator of carotid body activity; it can attenuate its sensory output via either a direct effect on glomus cells or dilatation of blood vessels, thus increasing carotid body blood flow (Brognara et al., 2021; Campanucci & Nurse, 2007; Campanucci et al., 2012; Wang et al., 1993).…”
Section: Introductionmentioning
confidence: 99%